2018
DOI: 10.3390/geosciences8110391
|View full text |Cite
|
Sign up to set email alerts
|

A Calorimetric and Thermodynamic Investigation of the Synthetic Analogue of Mandarinoite, Fe2(SeO3)3·5H2O

Abstract: Thermophysical and thermochemical calorimetric investigations were carried out on the synthetic analogue of mandarinoite. The low-temperature heat capacity of Fe2(SeO3)3∙5H2O(cr) was measured using adiabatic calorimetry between 5.3 and 324.8 K, and the third-law entropy was determined. Using these Cp,mo(T) data, the third law entropy at T = 298.15 K, Smo, is calculated as 520.1 ± 1.1 J∙K–1∙mol–1. Smoothed Cp,moT values between T → 0 K and 320 K are presented, along with values for Smo and the functions [HmoT-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Its crystal structure was solved by Hawthorne [67], who defined it as a hexahydrate. However, this conclusion was recently questioned by Holzheid et al [68], who suggested for mandarinoite the chemical formula [69]. The Te analogue of the mineral, telluromandarinoite, Fe 2 (SeО 3 ) 3 •6H 2 O, was described by Back et al [70].…”
Section: Most Structurally Complex Se Mineralsmentioning
confidence: 99%
“…Its crystal structure was solved by Hawthorne [67], who defined it as a hexahydrate. However, this conclusion was recently questioned by Holzheid et al [68], who suggested for mandarinoite the chemical formula [69]. The Te analogue of the mineral, telluromandarinoite, Fe 2 (SeО 3 ) 3 •6H 2 O, was described by Back et al [70].…”
Section: Most Structurally Complex Se Mineralsmentioning
confidence: 99%